Pathways to Youth Activism Orientation in STEM: the Role of STEM Classroom Inclusivity and Motivational Beliefs. - Ozturk, Emine; Cerda-Smith, Jacqueline; Joy, Angelina; Mathews, Channing J.; Mulvey, Kelly Lynn (Journal of Youth & Adolescence, 2025)
Activism around science, technology, engineering, and mathematics (STEM) is a critical task to promote social justice and to develop sustainable and effective solutions to global problems (e.g., climate change) in contemporary society. The present study examines relationships between adolescents' perceptions of gender and ethnic classroom inclusivity, outcome expectancies, utility values, and activism orientation in STEM, grounded in the situated expectancy-value theory. Participants were 699 adolescents (50.2% boys, 47.8% White; M = 15.11 years, SD = 0.84) in the southeastern United States. A structural equation model with FIML estimation, multiple imputation with Bayesian analysis, and multigroup SEM analyses were utilized to test the hypothesized associations using two time points, controlling for sociodemographics and STEM grades. The findings revealed that adolescents' perceptions of STEM classroom inclusivity appeared to play an important role in shaping STEM expectancies and perceived value of STEM. Multigroup SEM analysis showed that ethnicity significantly moderates the effect of perceived STEM classroom inclusivity on STEM expectancies, suggesting the effect of inclusivity on expectancies is stronger for racially/ethnically majoritized adolescents as compared to racially/ethnically minoritized adolescents. Associations from STEM motivational beliefs to activism orientation revealed that adolescents with higher STEM utility values are more likely to have a higher orientation toward STEM activism. Adolescents' perceptions of STEM classroom inclusivity had an indirect positive effect on STEM activism orientation through STEM utility values. These findings provide support for the conceptual premise that classroom inclusivity can foster motivational beliefs, and activism orientation in STEM.